2020
DOI: 10.1128/jcm.00630-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the QIAstat-Dx Respiratory SARS-CoV-2 Panel, the First Rapid Multiplex PCR Commercial Assay for SARS-CoV-2 Detection

Abstract: 33In the race to contain SARS-CoV-2, efficient detection and triage of infected patients must 34 rely on rapid and reliable testing. In this work we performed the first evaluation of the 35 QIAstat-Dx Respiratory SARS-CoV-2 Panel (QIAstat-SARS) for SARS-CoV-2 detection. This 36 assay is the first rapid multiplex PCR (mPCR) assay including SARS-CoV-2 detection, and is 37 fully compatible with a non-PCR trained laboratory or point-of-care (POC) testing. 38 This evaluation was performed using 69 primary clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 11 publications
3
93
0
2
Order By: Relevance
“…The molecular chemistry of INAAT is more complex than that of RT-PCR, involving more primers and intricate conformational rearrangements through enzymatic strand displacement, emphasizing the importance of target selection and primer design to performance. Another possible explanation is the potentially poorer performance of the RdRp target used in the Abbott assay than of other RNA targets as has been described previously (15,16). Recent reports indicate that mutations in the RdRp domain have been emerging (17).…”
Section: Discussionmentioning
confidence: 98%
“…The molecular chemistry of INAAT is more complex than that of RT-PCR, involving more primers and intricate conformational rearrangements through enzymatic strand displacement, emphasizing the importance of target selection and primer design to performance. Another possible explanation is the potentially poorer performance of the RdRp target used in the Abbott assay than of other RNA targets as has been described previously (15,16). Recent reports indicate that mutations in the RdRp domain have been emerging (17).…”
Section: Discussionmentioning
confidence: 98%
“…An increasing number of in-house and commercial COVID-19 RT-PCR assays have been described in the past 5 months [14][15][16][17][18][19][20][21][22][23][24][25][26]. The commercially available LightMix® Modular SARS and Wuhan CoV Egene kit is widely used in clinical laboratories, but its performance has not been thoroughly evaluated with clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In 69 clinical samples analysis, the overall consistent percentage of QIAstat-DX SARS and RT-PCR recommended by WHO was 97%, with a specificity of 93% (27/29) and a sensitivity of 100% (40/40). No cross-reactions of other respiratory viruses or bacteria were observed in this assay [62]. The results indicated that QIAstat-Dx Respiratory SARS-CoV-2 Panel has a comparable sensitivity to RT-PCR assay.…”
Section: Portable Benchtop-sized Analyzersmentioning
confidence: 73%